2021
DOI: 10.3389/fonc.2021.736882
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa PcrV Enhances the Nitric Oxide-Mediated Tumoricidal Activity of Tumor-Associated Macrophages via a TLR4/PI3K/AKT/mTOR-Glycolysis-Nitric Oxide Circuit

Abstract: Tumor-associated macrophages (TAMs), which display a tumor-supportive M2 phenotype, are closely related to tumor growth and metastasis. The reprogramming of TAMs toward a tumoricidal M1 profile has emerged as an attractive strategy for cancer immunotherapy. In this study, we found that the intratumoral injection of PcrV protein, a component of the Pseudomonas aeruginosa type 3 secretion system, suppressed tumor growth and increased apoptosis, inducible nitric oxide synthase (iNOS) expression, and the percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In recent years, insights into the critical role of metabolic adaptation in macrophage phenotype have emerged. [21] Studies have suggested that inhibition of glycolysis by 2-DG modulates macrophage polarization, increasing levels of ARG1 and decreasing expression of iNOS [19,55]. In addition, PKM2 is an essential molecular determinant of the Warburg effect and bridges metabolic and inflammatory functions [33,49].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, insights into the critical role of metabolic adaptation in macrophage phenotype have emerged. [21] Studies have suggested that inhibition of glycolysis by 2-DG modulates macrophage polarization, increasing levels of ARG1 and decreasing expression of iNOS [19,55]. In addition, PKM2 is an essential molecular determinant of the Warburg effect and bridges metabolic and inflammatory functions [33,49].…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of the fourth-stage larval Angiostrongylus cantonensis inhibited glycolysis and induced to M2 macrophages through PI3K/Akt pathway [14]. Pseudomonas aeruginosa induced to M1 macrophages and increased glycolysis of tumor-associated macrophages ability [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that numerous macrophages gathered around the lesion in AE patients, but the disease was still getting worse, and both M1 and M2 macrophages were signi cantly higher in close liver issue (CLT) than in distant liver tissue (DLT) from the lesion [12]. Pathogen infection modulated macrophages polarization through metabolic reprogramming by the PI3K/Akt/mTOR signaling pathway [14,15]. E. multilocularis infection changed glucose metabolism, macrophage polarization and PI3K/Akt/mTOR signaling pathways [11,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, a clinically used Toll-like receptor 4 agonist, monophosphatidyl lipid A, facilitated the transition from OXPHOS to glycolysis by activating mTOR signaling (63); on the other hand, Metformin (Met) shifted the state of TAMs to the M1 type by targeting and inducing a decrease in OXPHOS while increasing glycolysis (64). A Pseudomonas aeruginosa protein, PcrV, increased glycolytic activity and promoted the conversion of TAMs to the M1 type by activating the PI3K/AKT/mTOR signaling pathway, and the resulting increase in nitric oxide-related cytotoxicity induced Lewis lung carcinoma cell apoptosis (65). Furthermore, the anti-malarial drug chloroquine promotes the reprogramming of TAM metabolism from OXPHOS to glycolysis by increasing the lysosomal pH of macrophages, releasing Ca 2+ through the lysosomal Ca 2+ channel mucus-1, inducing the activation of p38 and NF-κB, and activating transcription factor EB (TFEB), which in turn polarizes TAMs from the M2 to the anti-tumor M1 phenotype (66).…”
Section: Effect Of Metabolic Reprogramming Of Tams On Their Polarizat...mentioning
confidence: 99%